The Effectiveness of Using the Guided-Discovery Style in the Development of Students' Attitudes toward Sports - Hame, Ahmed Q.M. (Humanities Journal of University of Zakho, 2016)
The research aims to identify the trends of high school students towards physical activity, and to find the significance of differences in those trends depending on the variables of specialization, sex and grade-level, as well as recognizing the impact of the use of guided discovery approach in the development of students' attitudes toward physical activity. The sample consisted of 160 students, who were selected from two high schools, one for males and another for females. Kenyon's Scale of trends toward physical activity was applied on the subjects of the study (the scale was translated or localized into Arabic by Mohammad Hassan Allawi, who applied it two pre and post-tests. The scale consists of 54 items distributed on six dimensions and in front of each paragraph; there are five alternatives to answer. The scale's validity and reliability has been verified. The research depends on the quasi-experimental design. The data were processed using the t-test for one sample and two, as well as the unilateral analysis of variance and Pearson correlation coefficient. The results showed that the sample members have a positive trend towards activity sports in all its dimensions. No significant differences in the trend depending on the specialization were seen, while the differences between the sexes appeared in four dimensions of the scale, showing a difference in just one depending on the grade level. The results indicated the presence of significant difference between the pre-test and post-test in all dimensions which shows the positive impact of the use of Guided-Discovery Approach. The researcher presented a series of recommendations and suggestions regarding the use of guided discovery approach in teaching physical education.